Walai - Arumpac, Adjani Guerrero 1984-
"The documentary films is an exploration of space. Literally, the film roams the space inside a home called the White House along Sinsuat Avenue in Cotabato City. Metaphorically, it prods on the memories of four women. The first is Bai Lily Sinsuat, the first wife of Datu Zekie Sinsuat, the infamous patriarch who owned the White House. The second is Annisa Sinsuat, the wife Datu Ahmed Sinsuat who is the youngest son of Bai Lily and Datu's Zekie. The third and fourth ones are Alhma and Ahmeda, the daughters of Annisa and Ahmed. The characters of these women will be honed for the audience through their stories about White House, a ruined space that was once their home. The documentary seeks narratives in "places...we tend to feel without history". (Rabinow, 1984: 139) It traces the past through the women's experience of what has happened inside the wrecked home - nostalgia and fear, loss and love and birth and death. It is a peek into the intimate lives of my female kin who continue to live in a culture that has long been subjected to misunderstanding and discrimination."